Antifungal Activity against Filamentous Fungi of Ts1, a Multifunctional Toxin from Tityus serrulatus Scorpion Venom - Santussi, Welligton M.; Bordon, Karla C. F.; Rodrigues Alves, Ana P. N.; Cologna, Camila T.; Said, Suraia; Arantes, Eliane C. (Frontiers in Microbiology, 2017)
Antimicrobial peptides (AMPs) are ubiquitous and multipotent components of the innate immune defense arsenal used by both prokaryotic and eukaryotic organisms. The search for new AMPs has increased in recent years, due to the growing development of microbial resistance to therapeutical drugs. In this work, we evaluate the effects of Tityus serrulatus venom (Tsv), its fractions and its major toxin Ts1, a beta-neurotoxin, on fungi growth. The fractions were obtained by ion-exchange chromatography of Tsv. The growth inhibition of 11 pathogenic and non-pathogenic filamentous fungi (Aspergillus fumigatus, A. nidulans, A. niger, A. terreus, Neurospora crassa, Penicillium corylophilum, P. ochrochloron, P. verrucosum, P. viridicatum, P. waksmanii and Talaromyces flavus) was evaluated by quantitative microplate reader assay. Tsv (100 and 500 µg/well, which correspond to 1 and 5 mg/mL, respectively, of total soluble protein) was active in inhibiting growth of A. nidulans, A. terreus, P. corylophilum and P. verrucosum, especially in the higher concentration used and at the first 30 h. After this period, fungi might have used Tsv components as alternative sources of nutrients, and therefore, increased their growth tax. Only fractions IX, X, XI, XIIA, XIIB (3 and 7.5 µg/well, which correspond to 30 and 75 µg/mL, respectively, of total soluble protein) and Ts1 (1.5, 3 and 6 µg/well, which correspond to 2.18, 4.36 and 8.72 µM, respectively) showed antifungal activity. Ts1 showed to be a nonmorphogenic toxin with dose-dependent activity against A. nidulans, inhibiting 100% of fungal growth from 3 µg/well (4.36 µM). The inhibitory effect of Ts1 against A. nidulans growth was accompanied by fungistatic effects and was not amended by 1 mM CaCl2 or tetrodotoxin (46.98 and 93.96 µM). The structural differences between Ts1 and drosomycin, a potent cysteine-rich antifungal peptide, are discussed here. Our results highlight the antifungal potential of the first cysteine-containing scorpion toxin. Since Ts1 is a multifunctional toxin, we suggest that it could be used as a template in the design of engineered scorpion antimicrobial peptides and in the search for new mechanisms of action of antifungal drugs.